Sacral neuromodulation outcomes in the management of lower urinary tract symptoms in multiple sclerosis patients - Tyler Trump; Po-Ming Chow; Vivian Hua; Omer Anis; Mazen Mansour; Howard B. Goldman (Continence)
INTRODUCTION/OBJECTIVE:: Multiple sclerosis (MS) is a common immune mediated disease of the central nervous system. The majority of patients will experience bothersome lower urinary tract symptoms (LUTS) over the course of their lifetime. Overactive bladder (OAB) symptoms are the most common followed by obstructive voiding symptoms and incomplete emptying. With disease progression, symptoms often change rendering previously effective therapies less effective. The objective of this study is to evaluate sacral neuromodulation (SNM) in the management of LUTS in MS patients METHODS:: Retrospective chart review of patients with a diagnosis of MS undergoing SNM between 2013–2022. Demographics, indication for SNM, and outcomes were recorded. The primary endpoint was success rate as defined as progression from test phase to implantable pulse generator (IPG) insertion. Secondary endpoints included factors associated with progression to IPG implant and sustained treatment efficacy. Sustained treatment efficacy was recorded at time of last follow-up encounter based on the global response assessment (GRA) with <50% indicating decreased efficacy and >50% indicating sustained efficacy. RESULTS:: We analyzed 58 patients with MS undergoing SNM. Demographics are summarized in Table 1. Mean follow-up was 6.1 years. Urinary urgency/frequency was the most common indication for placement with 40 patients (69%) compared to non-obstructive urinary retention (NOUR) with 18 patients (31%). 49/58 patients progressed to IPG implant for overall success rate of 84.5%. Success rate was higher for urinary urgency/frequency at 95% (38/40) compared to NOUR at 61% (11/18) (p=0.01). More patients underwent stage 1 trial (47/58) than peripheral nerve evaluation (11/58). Success rate was similar between trial types (83% and 90.9%, respectively) (p=0.085). NOUR was associated with decreased odds of success. BMI was positively correlated with success. Of the 49 patients who received IPG 25 (51%) were noted to have sustained efficacy. No factors were associated with sustained efficacy. CONCLUSION:: SNM provides meaningful improvement in LUTS of MS patients with a success rate of 84.5% in our cohort. OAB symptoms were noted to be more amenable to SNM than non-obstructive urinary retention. Roughly half of patients will maintain efficacy with continued therapy.